The Development of Reading and Writing Ability in English Vocabulary by Using Mind-map-based Learning Management and Games for Grade 3 Students - Nuangnorach, Pajaree; Thaweeboon, Samon (Academic MCU Buriram Journal, 2024)
This purpose of this research were 1) to develop the English vocabulary, reading, and writing skills of Grade 3 pupils at Ban Muang Tao School. This study aims to assess the English vocabulary reading and writing skills of Grade 3 pupils at Ban Muang Thao School, using the criterion of 80/80 for effectiveness (E1/E2). 2) to compare achievement in reading and writing English vocabulary. of students in Grade 3 at Ban Muang Tao School Between before studying and after studying and 3) before schooling and after studying, the investigation was conducted on a sample group of 3rd-grade pupils from Ban Muang Tao School, The Ubon Ratchathani Primary Educational Service Area Office, Area 2, Semester 1, Academic Year 2023. The sample group consisted of 16 students selected using purposive sampling, with the classroom as the randomization unit. The utilized tools consist of: 1) five learning management plans. 2) Academic achievement test on reading and writing English vocabulary Grade 3 is a multiple choice test with four options and 20 questions, has a difficulty value (p) between 0.24-0.69, has a discriminatory power value (B) between 0.30-0.60, and has a reliability value for the entire document equal to 0.91. 3) competency evaluation forms engaging in comprehending and producing written language consisting of 30 lexical units in the English language, has a difficulty value (p) between 0.33-0.69, has a discriminatory power value (B) between 0.30-0.55, and has a reliability value for the entire document equal to 0.94 and utilizing computer programs to analyze data. The measurements of statistics used in data analysis include percentage, mean, standard deviation, and dependent t-test. The research results found that: The Development of Reading and Writing Ability in English Vocabulary by Using Mind-map-based Learning Management and Games for Grade 3 Students, the results can be summarized as follows. 1. Basic learning plan for reading and writing English vocabulary for Grade 3 students with mind maps and language games has an efficiency of 88.94/85.63, which meets the specified criteria. 2. The achievement in reading and writing English vocabulary of 3rd year primary school students after studying is higher than before studying. Statistically significant at the .01 level. 3. The ability to read and write English vocabulary of 3rd year primary school students after studying is higher than before studying. Statistically significant at the .01 level.